Analisis Antonimi dalam Berita Hiburan Alarabiya.net - Muhammad Fadhlurrahman Zakaria (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research aims to describe the forms of variation and types of antonymy in entertainment news texts on the Alarabiya news site. This research was carried out by collecting pairs of Arabic antonymies in news texts which have been analyzed semantically in the form of a classification based on types of Arabic antonymy. The theory that is the basis for the object of this research is the theory of an Arab linguist, Muhammad Ali al-Khuli. This theory classifies that antonymy is divided into 9 types, of which in this research we got 2 examples of each type